Case Report: Decitabine and venetoclax sequentially followed by FLAG-Ida and venetoclax with immediate allogeneic stem cell transplantation in newly diagnosed acute myeloid leukemia with chromosome 3 inversion/MECOM rearrangement - Žučenka, Andrius; Tamutytė, Milvydė (Frontiers in Oncology, 2025)
The prognosis of MECOMr AML is poor, with a 5-year overall survival (OS) rate of less than 10%. This is mostly attributable to the low efficacy of all available therapies and high relapse rates even after allogeneic stem cell transplantation (alloSCT), which remains the only curative approach. We report upfront sequential alloSCT with venetoclax-based preconditioning as a safe and effective treatment for two newly diagnosed and fit MECOMr AML patients. The sequential alloSCT regimen consisted of triple therapy: preconditioning with decitabine and venetoclax on days 1–5 followed by FLAG-Ida and venetoclax on days 6–10. One or 3 days after preconditioning, the patients underwent busulfan-based myeloablative conditioning and HLA haploidentical or matched related donor stem cell infusion. One month after alloSCT, timely engraftment and complete remission were achieved. At the last follow-up, both patients were in good health and in MRD-negative complete remissions after 11 and 17 months after alloSCT, respectively. The safety and efficacy of upfront sequential alloSCT indicate the need to evaluate this approach for adverse risk of AML in clinical trials.